A multifaceted interplay between virulence, drug resistance, and the phylogeographic landscape of Mycobacterium tuberculosis - Igor Mokrousov; Tatiana Vinogradova; Marine Dogonadze; Natalia Zabolotnykh; Anna Vyazovaya; Maria Vitovskaya; Natalia Solovieva; Boris Ariel (Microbiology Spectrum, 2023)
ABSTRACT Latin-American Mediterranean (LAM) family is one of the most significant and global genotypes of Mycobacterium tuberculosis. Here, we used the murine model to study the virulence and lethality of the genetically and epidemiologically distinct LAM strains. The pathobiological characteristics of the four LAM strains (three drug resistant and one drug susceptible) and the susceptible reference strain H37Rv were studied in the C57BL/6 mouse model. The whole-genome sequencing was performed using the HiSeq Illumina platform, followed by bioinformatics and phylogenetic analysis. The susceptible strain H37Rv showed the highest virulence. Drug-susceptible LAM strain (spoligotype SIT264) was more virulent than three multidrug-resistant (MDR) strains (SIT252, SIT254, and SIT266). All three MDR isolates were low lethal, while the susceptible isolate and H37Rv were moderately/highly lethal. Putting the genomic, phenotypic, and virulence features of the LAM strains/spoligotypes in the context of their dynamic phylogeography over 20 years reveals three types of relationships between virulence, resistance, and transmission. First, the most virulent and more lethal drug-susceptible SIT264 increased its circulation in parts of Russia. Second, moderately virulent and pre-XDR SIT266 was prevalent in Belarus and continues to be visible in North-West Russia. Third, the low virulent and MDR strain SIT252 previously considered as emerging has disappeared from the population. These findings suggest that strain virulence impacts the transmission, irrespective of drug resistance properties. The increasing circulation of susceptible but more virulent and lethal strains implies that personalized TB treatment should consider not only resistance but also the virulence of the infecting M. tuberculosis strains. IMPORTANCE The study is multidisciplinary and investigates the epidemically/clinically important and global lineage of Mycobacterium tuberculosis, named Latin-American-Mediterranean (LAM), yet insufficiently studied with regard to its pathobiology. We studied different LAM strains (epidemic vs endemic and resistant vs susceptible) in the murine model and using whole-genome analysis. We also collected long-term, 20-year data on their prevalence in Eurasia. The findings are both expected and unexpected. (i) We observe that a drug-susceptible but highly virulent strain increased its prevalence. (ii) By contrast, the multidrug-resistant (MDR) but low-virulent, low-lethal strain (that we considered as emerging 15 years ago) has almost disappeared. (iii) Finally, an intermediate case is the MDR strain with moderate virulence that continues to circulate. We conclude that (i) the former and latter strains are the most hazardous and require close epidemiological monitoring, and (ii) personalized TB treatment should consider not only drug resistance but also the virulence of the infecting strains and development of anti-virulence drugs is warranted.